Comparative Analysis of Filler Wall Interlock System Using Three Different Wall Material Using ETABS A Review - Sandeep Kumar Gupta; Pradeep Kumar Nimal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
A reinforced concrete building with masonry infill is most common type of construction in India. Traditionally, conventional clay bricks or concrete blocks which are heavy rigid materials have been used as Infill wall. Though, AAC (aerated light weight concrete) blocks which are lightweight, flexible building materials that provides insulation and fire resistance and have lower impact on environment, can be used as masonry infill (MI) material in buildings. AAC blocks are now also available in India. A number of researchers have studied the behavior of AAC in-filled reinforced concrete (R/C) frames experimentally. Interlocking Bricks are even introduced further which adds an advantage over AAC bricks.
Keywords: Interlocking Blocks; AAC Block; Infill Frame; Equivalent Strut Model